THE IMPACT OF INNOVATION STRATEGY TOWARD BUSINESS COMPETITIVENESS OF MANUFACTURING INDUSTRY IN SURABAYA, INDONESIA - Slamet Riyadi; Sumardi Sumardi (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2017)
This study aimed to examine and analyze the effect of administrative innovation on business competitiveness, technical innovations on business competitiveness, process innovation on business competitiveness, and product innovation on business competitiveness. This research conducted at manufacturing industry in Surabaya City, Indonesia. The number of samples was 100 business units, where the top manager or middle managers as the respondent. Methods of analysis use both descriptive statistical and Structural Equation Model (SEM). Data processed by IBM AMOS software. The results show that innovation strategy which consists of administrative innovation, technical innovation, process innovation, and product innovation can enhance organizational competitiveness in the manufacturing industry context. Administration innovation has a positive effect on business competitiveness. Technical innovation has a positive effect on business competitiveness. Process innovation has a positive effect on business competitiveness. Then, product innovation has a positive effect on business competitiveness. Process innovation has greater influence in improving business competitiveness compared to other innovation strategies.